SIFAT-SIFAT RUANG TOPOLOGI T_2Δ - Erik Maurten Firdaus; Ade Ima Afifa Himayati (Universitas Muhammadiyah Kudus, 2023)
A topological space is called if is a spaces and for every open set and In this paper, we investigate some properties of space. We study hereditary, topological invariant, and the product of finite spacesA topological space is called if is a spaces and for every open set and In this paper, we investigate some properties of space. We study hereditary, topological invariant, and the product of finite spaces